THROUGH LEGAL EDUCATION TOWARDS A EUROPEAN EDUCATION AREA - Kasap, Jelena; Lachner, Višnja; Žiha, Nikol (EU and comparative law issues and challenges series (ECLIC), 2018)
With special focus on laying the foundations for a European Education Area by 2025, “The first European Education Summit˝, held on 25 January 2018, aimed at determining how quality, inclusive and values-based education can fight the current challenges and contribute to a successful Europe. Although the primary competence for education policies lies with the Member States, the European Commission has explicitly advocated that joint efforts should be made to strengthen the European identity through education. In particular, a number of initiatives were proposed in order to foster employability in the common market, improve the international competitiveness, promote common values and develop critical thinking for an active citizenship. For all these reasons, this paper aims at determining how Croatian legal education, taking into account its tradition, can contribute to achieving those objectives. Therefore, by analyzing its history and tradition, the first part of the contribution will try to identify the specific features of Croatian higher legal education. Keeping in mind that the success of the process is often influenced by various social, political, economic and historical factors, the central part of the paper will examine the importance of education for shaping the national legal culture and, consequently, efficient harmonization. Considering the challenges that the Croatian educational system is currently facing, as a conclusion, an attempt will be made to offer some preliminary solutions in the debate on how the potential of education can be used to ensure the goals of the European Education Area.